(3GdeHGMK GdMSGf GdeQahYI Edi bGVi JdeSGf (B[ (3GdTjN TYjH Hf Ydi GdLdjdi GdeJhaj HYO (B1350(3g`(B]s - (3GdcJGfj , eMeO Hf YHO GdcHjQ Hf eMeO, CHh GdajV CHh YHO Gddg,J (B1327 (3g` s
(3ChdgG (B:s
(3ef NGOe GdMOjK eMeO YHO GdMi Edi bGVi JdeSGf TYjH Hf Ydi ef CYXe eG MUd di Hg GdZHWI eGJMbbJg ef GJUGaGce HeWGdYI dWja LhGHce s
(3BNQgG (B:s
(3CHbGce Gddg PNQkG ddYHGO Bejf , hGdSdGe Ydi SjGOJce s
(3Vef eLehY , JQJjHgG (B: (3ef U (B372 - (3U(B395s
(3Odjd eDQN GdeZQH U`(B334s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B185s
(3Odjd eDQN GdeZQH (B- (3U (B334 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B364 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(68 (3c(B) s
Keywords: (3GdJGQjNs